Utilization of regional assets as an instrument for increasing local own-source revenue (PAD) in North Toraja Regency - Jemi Pabisangan Tahirs (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The management of regional assets plays a strategic role in increasing Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) and strengthening regional fiscal independence. This study aims to analyze the utilization of regional assets as an instrument for increasing PAD in North Toraja Regency, identify constraints in asset management, and formulate effective asset optimization strategies. This research employs a qualitative method with a descriptive and inductive approach. Data were collected through interviews, observations, and documentation involving informants from local government officials, members of the Regional House of Representatives (DPRD), and communities directly affected by regional asset utilization. The results indicate that most regional assets in North Toraja Regency have not been optimally utilized due to weak asset inventory systems, limited human resources, unclear legal status of assets, and insufficient coordination among regional government agencies. Nevertheless, several strategies—such as asset re-inventory, digitalization of asset management, cooperation with third parties, and the involvement of Village-Owned Enterprises (BUMDes)—have proven to positively contribute to the increase in PAD. Asset optimization also generates broader impacts, including the stimulation of local economic activities, job creation, and improvements in transparent and accountable asset governance. This study concludes that optimizing regional assets requires an integrated strategic approach supported by clear regulations, the use of information technology, capacity building of human resources, and collaboration with the private sector and BUMDes. Through these strategies, regional assets can become sustainable sources of revenue while supporting regional economic development in North Toraja Regency.